INCREASING INSTITUTIONAL EFFICIENCY OF ECONOMIC SYSTEM AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF UKRAINE - O. Demydiuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper studies the problem of institutional efficiency of the economic system of Ukraine in the context of sustainable development. The study shows features of the institutional matrix of the economic system of Ukraine. The results highlight ways of increasing the institutional efficiency of the national economy.